Peningkatan Sikap Positif Terhadap Purpose In Life Dengan Bimbingan Kelompok Teknik Role Playing - Ridia Dinata; Yusmansyah Yusmansyah; Moch Johan Pratama (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
The purpose of the research was to increase a positive attitude towards psychological well-being in terms of purpose in life. The method used in this study is quasi-experimental design of untreated control group design with dependent pretest and posttest. The research subjects were an experimental group of 10 people and a control group of 10 people. Data collection techniques use a scale of purpose in life attitude. The results showed that positive attitudes towards students' purpose in life can be improved through role playing technique group guidance services, this is indicated by the Mean Whitney test results with values (Sig.) 0.000 0.05, then Ho is rejected Ha accepted, meaning that there is an increase of positive attitude towards purpose in life after being given role playing technique group guidance services in the experimental group. The conclusion is that the positive attitude of students towards purpose in life can be improved by using role playing technique group guidance services in the experimental group of grade XI students of SMK Negeri 4 Bandar Lampung Academic Year 2018/2019.Tujuan penelitian untuk meningkatkan sikap positif terhadap kesejahteraan psikologis dimensi purpose in life. Metode yang digunakan dalam penelitian ini adalah quasi eksperimen desain untreated control group design with dependent pretest and posttest. Subjek penelitian adalah kelompok eksperimen sebanyak 10 orang dan kelompok kontrol sebanyak 10 orang. Teknik pengumpulan data menggunakan skala sikap purpose in life. Hasil penelitian menunjukkan bahwa sikap positif terhadap purpose in life siswa dapat ditingkatkan melalui layanan bimbingan kelompok teknik role playing, hal ini ditunjukkan hasil uji Mean Whitney dengan nilai (Sig.) 0,000 0,05, maka Ho ditolak Ha diterima, artinya bahwa terdapat peningkatan sikap positif terhadap purpose in life setelah diberikan layanan bimbingan kelompok teknik role playing pada kelompok eksperimen. Kesimpulannya adalah sikap positif siswa terhadap purpose in life dapat ditingkatkan menggunakan layanan bimbingan kelompok teknik role playing pada kelompok eksperimen siswa kelas XI SMK Negeri 4 Bandar Lampung Tahun Pelajaran 2018/2019.Kata kunci: bimbingan dan konseling, teknik role playing, purpose in life